SReactivation of CeO2‐based Catalysts in the HCl Oxidation Reaction: In situ Quantification of the Degree of Chlorination and Kinetic Modeling. Issue 21 (9th September 2020) - Sun, Yu; Hess, Franziska; Djerdj, Igor; Wang, Zheng; Weber, Tim; Guo, Yanglong; Smarsly, Bernd M.; Over, Herbert
Abstract: Deactivation of CeO2 ‐based catalysts in the HCl oxidation reaction proceeds via selective bulk chlorination of the active CeO2 component to form CeCl3 ×nH2 O. We study the reactivation of two bulk‐chlorinated CeO2 ‐based Deacon catalysts by oxygen treatment at 430 °C, namely pure CeO2 and 20 mol % of CeO2 supported on preformed ZrO2 particles (20CeO2 @ZrO2 ), with a dedicated experiment. In the flow reactor setup we determine in‐situ the degree of chlorination of the catalyst by quantifying down‐stream with in‐situ UV‐Vis spectroscopy the total amount of chlorine in the catalyst that is exchanged by reoxidation at 430 °C. The activity of deactivated 20CeO2 @ZrO2 can be fully restored by oxygen exposure at 430 °C, while that of pure CeO2 declines steadily. Since the UV‐Vis analytics is fast and sensitive, we can follow the kinetics of reoxidation. To rationalize the observed kinetics, we develop a modified Johnson‐Mehl‐Avrami‐Kolmogorov (JMAK) model based on a nucleation‐and‐growth approach for the reoxidation of the catalyst starting from the chlorinated phase. The fast reoxidation kinetics of chlorinated 20CeO2 @ZrO2 is traced to a fast nucleation rate. Abstract : Remain dispersed : A dedicated experiment is devised for quantifying the chlorination degree of the CeO2 ‐based catalyst in the same reactor in which also the catalytic HCl oxidation reaction is performed so that we can follow in‐situ the kinetics of the reactivation of a bulk‐chlorinated CeO2 ‐based samples, pure CeO2 and the other is 20 mol % CeO2 supported on preformed ZrO2 particles, via reoxidation. In a phenomenological model, we describe the faster reoxidation of the supported catalyst by a higher nucleation rate at ZrO2 .